Impact of Some Heavy Metals and BPA Resulting from Terrorist Operations in Three Regions of Baghdad, Iraq on Serotonin‎ - Jawad, Alaa H (Al-Nahrain Journal of Science, 2018)
In this paper the effect of terrorist operations in three regions of Baghdad, Iraq were studied on serotonin hormones, in 75 Iraqi individual from (AL-karradah and Abo-Gharib) regions as comparison with Al-jadria as (a control). The correlation between sera serotonin and the levels of lead (Pb), cadmium (Cd), mercury (Hg) and bisphenol-A(BPA) have been selected for study, relation of heavy metals, BPA and monoamine neurotransmitter frameworks has been recommended as a potential underline component of action. The serotonin framework has been moderately ignored, along these lines; the objective of this article is to audit the writing on the connection between heavy metals, BPA and the serotonin. Our examination proposes a positive ‎correlation between serotonin and the levels of lead (Pb), cadmium (Cd), mercury (Hg) and BPA. In conclusion, that serotonin levels in the area of (Al-karadah, Abo-Gharib) pollutants areas were high as compared with the control (Al-jadria) as the lowest percentage of pollution. Thus considerable further investigation will be necessary to understand the role of serotonin in the pathogenesis and high levels in the some regions in Iraq such as AL-karradah and Abo-Gharib.